Searching for potential wood biomass for green energy feedstock: A study in tropical swamp-peat forest of Kutai Kertanegara, Indonesia - RUDIANTO AMIRTA; MUHAMMAD TAUFIQ HAQIQI; SAPARWADI SAPARWADI; ELIS SEPTIA; DEWI MUJIASIH; KRISNA ADIB SETIAWAN; MUHAMMAD AFIF SEKEDANG; YULIANSYAH YULIANSYAH; AKHMAD WIJAYA; BUDHI SETIYONO; WIWIN SUWINARTI (Society for Indonesian Biodiversity, 2019)
Abstract. Amirta R, Haqiqi MT, Saparwadi, Septia E, Mujiasih D, Setiawan KA, Sekedang MA, Yuliansyah, Wijaya A, Setiyono B, Suwinarti W. 2019. Searching for potential wood biomass for green energy feedstock: A study in tropical swamp-peat forest of Kutai Kertanegara, Indonesia. Biodiversitas 20: 1516-1523. Recently, much attention has been focused on finding suitable plant species, from different forest ecosystems, having the potential to be used as sources of renewable energy. Most of such information was reported from the lowland forest area and only limited information is available regarding swamp-peat forest species, including their energy potency. Therefore, in this paper, plant diversity and energy potency of swamp-peat forest wood biomass were studied to reveal their potential as green energy feedstock. Physico-chemical characterization of wood biomass was performed using the American Society for Testing and Material (ASTM) protocols. Twenty-seven species of plants, consisting of 23 trees and 4 shrubs, belonging to 19 families were identified, amongst which Shorea balangeran had the highest importance value index (87.72%). The results showed that T. obovata exhibit the highest suitability to be used as energy feedstock indicated by the highest energy production of 4.60 MWh per ton of dry biomass, followed by L. indica (4.56 MWh/ton), D. excelsa (5.52 MWh/ton), F. rukam (4.20 MWh/ton), P. galeata (3.66 MWh/ton), S. caudatilimbum (3.61 MWh/ton), A. elmeri (3.59 MWh/ton), G. nervosa (3.49 MWh/ton) and G. bancana (3.42 MWh/ton). The high density of wood species correlated with the high value of energy potency. In contrast, the fast-growing tree and shrub species, such as K. hospita (1.76 MWh/ton), C. odorata (1.36 MWh/ton) and O. sumatrana (1.17 MWh/ton), showed lower energy potency. The most dominant plant species, S. balangeran gave only 2.96 MWh energy per ton of dry biomass and it was classified in the middle group of plant species suitable as green energy feedstock, along with other species, such as C. brachiata, C. rotundatus, P. javanicum, V. umbonata, L. speciosa, V. pinnata, and A. longifolius. Due to suitable energy properties, growth rate and also adaptability of this woody biomass, they can be exploited to support sustainable supply of biomass feedstock for the green electricity program in the study area.